2020
DOI: 10.3390/jcm9010130
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Obstructive Sleep Apnea: The Value of Sleep Questionnaires with a Separate Analysis of Cardiovascular Patients

Abstract: Background: Gender affects the clinical presentation of obstructive sleep apnea (OSA). The classic OSA symptoms, such as sleepiness, snoring, and apnea, are not so frequent in women. Objectives: To evaluate possible gender differences in questionnaires used for OSA prediction, such as the Epworth Sleepiness Scale (ESS), STOP, STOP Bang (SB), Berlin Questionnaire (BQ), Athens Insomnia Scale (AIS), and Fatigue Scale (FS). Methods: 350 males were matched with 350 women referred to a sleep clinic, according to OSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 36 publications
2
26
0
4
Order By: Relevance
“…Included studies showed low to moderate risk of bias after validity assessment and were used to answer our review question. Studies were organized into 6 groups: (1) North America (9 studies, 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 3507 participants); (2) South America (6 studies, 28 , 29 , 30 , 31 , 32 , 33 10 709 participants); (3) Europe (10 studies, 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 5679 participants); (4) the Middle East (11 studies, 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 3468 participants); (5) East Asia (4 studies, 55 , 56 , 57 , 58 1665 participants); and (6) South or Southeast Asia (7 studies, 59 , 60 , 61 , 62 , 63 , 64 , 65 1519 participants).…”
Section: Resultsmentioning
confidence: 99%
“…Included studies showed low to moderate risk of bias after validity assessment and were used to answer our review question. Studies were organized into 6 groups: (1) North America (9 studies, 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 3507 participants); (2) South America (6 studies, 28 , 29 , 30 , 31 , 32 , 33 10 709 participants); (3) Europe (10 studies, 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 5679 participants); (4) the Middle East (11 studies, 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 3468 participants); (5) East Asia (4 studies, 55 , 56 , 57 , 58 1665 participants); and (6) South or Southeast Asia (7 studies, 59 , 60 , 61 , 62 , 63 , 64 , 65 1519 participants).…”
Section: Resultsmentioning
confidence: 99%
“…While the mean BMI in our subjects was higher than 31 in both genders, other populations had a mean BMI lower than 30. 19 , 22 , 38 , 39 Putting all these factors together, the group of patients described in this study were from a high-altitude city, in a developing country, and they were older and more obese than those in most of the previous reports.…”
Section: Discussionmentioning
confidence: 87%
“… 17 , 22 , 37 , 39 Interestingly, two cohorts with BMI differences between the genders (female having a higher BMI than male) were younger cohorts than ours. 16 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Progress has already been made in the use of deep neural network analyses and other machine learning techniques to improve sleep and respiratory staging of the electroencephalogram and allow the determination of sleep stage and sleep-disordered breathing without electroencephalogram. 8 Note that large and diverse datasets are required for proper analyses because differences in sleep and sleep-disordered breathing because of ethnicity, 9,10 sex, 11 and age 12 are recognized. When linked to clinically relevant outcomes, novel machine learning analyses may lead to new diagnostic criteria and a deeper understanding of the impacts of disordered sleep.…”
mentioning
confidence: 99%